ANALISIS PENGARUH LAJU PERTUMBUHAN PENDUDUK, INDEKS PEMBANGUNAN MANUSIA, PERTUMBUHAN EKONOMI, DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP TINGKAT KEMISKINAN DI KABUPATEN PASURUAN DAN KABUPATEN GRESIK - Dewi Nuril Afifah; Niniek Imaningsih (Universitas Nias Raya, 2025)
Pasuruan Regency and Gresik Regency are two regions in East Java Province that have rapid industrial sector growth rates, but still face challenges in overcoming poverty problems. Although economic growth in both regions is quite high, the decline in poverty rates has not occurred evenly. This study aims to determine the effect of population growth rate, human development index (HDI), economic growth, and open unemployment rate (TPT) on poverty rates in Pasuruan Regency and Gresik Regency during the period 2004–2023. This study uses the dependent variable, namely the poverty rate (Y), and the independent variables, namely the population growth rate (X1), human development index (X2), economic growth (X3), and open unemployment rate (X4). The data used are secondary data obtained from the Central Statistics Agency of Pasuruan Regency, Gresik Regency, and East Java Province. The analysis method used is multiple linear regression analysis with the help of IBM SPSS software version 26. The results of the study indicate that the HDI and TPT variables have a significant effect on poverty rates in Pasuruan Regency, while the population growth rate and economic growth variables do not have a significant effect. Meanwhile, similar to Gresik Regency, the IPM and TPT variables have a significant effect on poverty, while the population growth rate and economic growth do not have a significant effect. This finding indicates that improving the quality of human resources and labor absorption have an important role in reducing poverty rates in the region.